The Impact of Cancer on the Clinical Outcome of Patients After Inferior Vena Cava Filter Placement: A Retrospective Cohort Study. (June 2016) - Narayan, Anand; Hong, Kelvin; Streiff, Michael; Shinohara, Russell; Frangakis, Constantine; Coresh, Josef; Kim, Hyun S.
Abstract : Objectives: Inferior vena cava (IVC) filters are placed to prevent pulmonary embolism, however, some studies have suggested that IVC filters are associated with exacerbated risks of deep vein/IVC thrombosis in cancer patients. The purpose of this study is to determine if cancer patients develop higher than expected rates of venous thromboembolism complications after filter placement compared with noncancer patients. Materials and Methods: A retrospective cohort study of consecutive patients who received filters (2002 to 2006) at Johns Hopkins was conducted. Exposures and outcomes were obtained by chart review. Relative risks (RR, 95% confidence interval [CI]) for outcomes in cancer versus noncancer patients were estimated using multistate models. Results: The cohort included 702 patients—246 with cancer and 456 without cancer. Cancer patients were older, more likely to be white and have filters placed for contraindications to anticoagulation ( P <0.01). The most common cancers were lung (11.8%) and colorectal (10.6%). Cancer patients had an increase in venous thromboembolism (RR 1.9 [95% CI, 1.1, 3.2]) due to more deep venous thrombosis/IVC thrombosis (RR 1.7 [95% CI, 1.0, 3.0]). Higher pulmonary embolism rates in cancer were not statistically significant (RR 2.2 [95% CI, 0.8, 5.8]). Conclusions: Cancer patients have elevated risks of thrombotic complications compared with noncancer patients; however, these risks are not higher than expected based on historical controls. Abstract : Supplemental Digital Content is available in the text.